THE ROLE OF TEACHERS IN GUIDING STUDENTS IN THE LEARNING PROCESS OF ISLAMIC EDUCATION DURING THE COVID 19 PANDEMIC AT THE MADRASAH TSANAWIYAH NEGERI TOBA SAMOSIR - Ayu Mardiyatin Zanah Nurhikmah; Munawir Pasaribu (Proceeding International Seminar of Islamic Studies, 2022)
The teacher is the main element that has an important role in formal education. Its existence is a determinant of the success of students and the quality of education. During the current Covid-19 pandemic, teachers are required to be able to demonstrate teacher competence in guiding, training, educating, and teaching their students. Learning is a very important thing as a source to achieve high knowledge, through science humans can find solutions and solve life problems both now and in the future, one of the elements that play an important role in good learning process activities and quality in the individual is motivation. Thus it can be understood that motivation in learning is something that is very instrumental in the activities of the process of seeking knowledge in individuals. In the Islamic perspective, its adherents are strongly encouraged to have high learning motivation, so that with high learning motivation, knowledge will be easily obtained. To increase motivation to learn in individuals, it can be done by guiding and following the advice of Islamic teachings, especially those related to rewards and glory in the sight of Allah for people who have knowledge. The purpose of this paper is to describe the importance of learning motivation in individual life, and matters relating to the Islamic view of learning motivation, as well as efforts to increase learning motivation. The method in this writing is a literature study, namely by describing and analyzing several Islamic theories and views on learning motivation. Teachers have various tasks that are implemented in the form of dedication. These tasks include the professional field, the humanitarian field and the social field. Tasks include educating teachers as a profession, teaching and training. Educating means continuing and developing the values of life and living. Teaching means continuing and developing science and technology while training means developing skills in students and teachers should be wise in the learning process, teachers should dress clean and neatly, teachers should evaluate their students.